Społeczeństwo obywatelskie Izraela wobec przemian politycznych - Obirek, Stanisław (Humaniora. Czasopismo Internetowe, 2024)
The purpose of the article is to present Israeli society in the face of political change. These culminated in the formation of the radical right-wing coalition of Benjamin Netanyahu’s government in December 2022. To understand the current polarization of Israeli society, it is necessary to recall the history of its establishment and political transformation from 1948 to 2022. The history of Zionism and its transformations after the establishment of the State of Israel in 1948 will be presented. The cut-off date will be the brutal Hamas attack on the State of Israel on October 7, the 50th anniversary of the outbreak of the Yom Kippur War on October 6, 1973.